THE STUDY OF SOME ANCIENT TURKISH TERMS IN THE WORK “DEVONU LUG‘AT AT TURK” (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this article, the literary terms in the work “Devonu lug'at at-turk” written by Mahmud Koshgari, an encyclopedic linguist, and their alternatives today are considered. It has been discussed what some ancient Turkish terms meant in the 11th century, how many of them have alternative versions, how many are in use, and how many have changed their meaning.